Evolution of HIV-1 Drug Resistance after Virological Failure of First-line Antiretroviral Therapy in Lusaka, Zambia. Issue 4 (May 2019) - Hudson, F Parker; Mulenga, Lloyd; Westfall, Andrew O; Warrier, Ranjit; Mweemba, Aggrey; Saag, Michael S; Stringer, Jeffrey SA; Eron, Joseph J; Chi, Benjamin H
Background: HIV viral load (VL) and resistance testing are limited in sub-Saharan Africa, so individuals may have prolonged time on failing first-line antiretroviral therapy (ART). Our objective was to describe the evolution of drug resistance mutations among adults failing first-line ART in Zambia. Methods: We analysed data from a trial of VL monitoring in Lusaka, Zambia. From 2006 to 2011, 12 randomized sites provided either routine VL monitoring (intervention) or discretionary (control) after ART initiation. Samples were collected prospectively following the same schedule in each arm but analysed retrospectively in the control group. For those with virological failure (VF; >400 copies/ml), HIV genotyping was performed retrospectively on baseline (BL) and on all subsequent specimens until censored due to study completion, withdrawal or death. Results: Of 1, 973 enrollees, 165 (8.4%) developed VF. 464 genotype results were available including 132 (80%) at BL, 116 (70%) at VF and 125 (76%) had at least one result between VF and censoring. Major nucleoside reverse transcriptase inhibitor (NRTI) or non-nucleoside reverse transcriptase inhibitor (NNRTI) mutations increased from 26% (BL) to 82% (VF) to 89% at last genotype (LG). M184 mutations increased from 2% to 59% to 71%; K65R from 2% to 11% to 13%; 2 or more thymidine analogue mutations from 1% to 3% to 12%. Among those on a failing tenofovir disoproxil fumarate (TDF)-based regimen, TDF resistance increased from 42% to 58%. Conclusions: We found substantial resistance to NRTIs and NNRTIs at VF with incremental increases after VF while still on a failing first-line ART; this resistance may compromise attainment of the UNAIDS 90-90-90 goals.